Concepts and Principles Of Teaching Foreign Languages In Primary Education: A Theoretical Approach - Abdullayeva, Madinabonu (Indonesian Journal Publisher, 2024)
This article explores the fundamental concepts and principles of teaching foreign languages in primary education, emphasizing its role in fostering cognitive and social skills in young learners. Additionally, the article outlines essential teaching principles, such as age-appropriateness, maintaining motivation, and creating a natural learning environment, effectiveness of game-based learning and examines challenges in early language instruction, including resource limitations and lack of trained educators, offering practical recommendations to address these issues and improve foreign language education outcomes in primary education.